Pincer Flap for Reconstruction of Nasal Tip Defects. Issue 3 (May 2016) - Inozu, Emre; Tellioglu, Ali Teoman; Eryilmaz, Avni Tolga; Ergin, Seven
Abstract : Introduction: Reconstruction of the nasal tip defects is challenging because of variable contours of the region and the unique texture, thickness, color, and limited amount of available skin. There are several well-known local flaps for this purpose. Unfortunately, most of these flaps are suitable for small sized defects up to 2 cm in diameter. In this study, the authors are presenting a new flap for reconstruction of nasal tip and supratip defects larger than 2 cm in diameter. Methods: Pincer flap was used for reconstruction of nasal tip defects in 12 patients, between 2011 and 2014. The mean age was 67 (43–88). All patients had a basal cell carcinoma. Defects were located at the central nasal, lateral nasal, and supratip areas. All tumors were excised with safe margins. After the excision, defects were reconstructed with pincer flap in the same session. Results: The mean follow-up period was 11 (6–18) months. There was not any flap loss. Infection and venous congestion was observed in 2 patients but the patient did not require any further surgical intervention, and healed with local and systemic antibiotherapy. No recurrence occurred and the outcome was aesthetically favorable. Conclusions: The authors concluded that pincer flap is reliable and may provide a single-stage reconstruction for the nasal tip defects larger than 2 cm and up to 3 cm in diameter.